2021
DOI: 10.1038/s41597-021-00834-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among 481 diverse soybean accessions, inferred from genomic re-sequencing

Abstract: We report characteristics of soybean genetic diversity and structure from the resequencing of 481 diverse soybean accessions, comprising 52 wild (Glycine soja) selections and 429 cultivated (Glycine max) varieties (landraces and elites). This data was used to identify 7.8 million SNPs, to predict SNP effects relative to genic regions, and to identify the genetic structure, relationships, and linkage disequilibrium. We found evidence of distinct, mostly independent selection of lineages by particular geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…The first step is to select a genotype collection. For soybean, we select the “USB 481” set, from Valliyodan et al (2020). This has good genome‐wide SNP density, and contains a good mix of G. soja and G. max accessions and elite and landrace lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step is to select a genotype collection. For soybean, we select the “USB 481” set, from Valliyodan et al (2020). This has good genome‐wide SNP density, and contains a good mix of G. soja and G. max accessions and elite and landrace lines.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype Comparative Visualization Tool (GCViT) view of selected soybean accessions from Valliyodan et al (2020). On the left of each chromosome, single nucleotide polymorphism (SNP) density is shown (as a gray histogram), for reference accession PI597458, from Glycine soja .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent analysis of an expanded soybean resequencing dataset of 775 accessions distributed between 110 G. soja and 665 G. max revealed a total of 15 G. soja and 2 G. max accessions with e1la :K82E alleles [ 23 , 25 ]. In our original analysis of the 302 soybean dataset, no variant alleles of the E1Lb gene were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The ten G. soja accessions also contained a synonymous variant (G/T) at Gm04:28,294,356 that was present in an additional 14 G. soja accessions. The soybean allele catalog ( http://soykb.org/GenescapeAnalysis/search.php ) was used to assess the distribution of alleles of E1La and E1Lb in our curated data set of 775 whole genome re-sequenced soybean accessions [ 23 , 25 ]. A protein blast at NCBI, using the Williams 82 reference peptide sequence of E1La , was used to obtain the orthologous sequences from 23 different legume species with the highest percent identity (Supplemental Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Valliyodan et al. (2021) analyzed genetic diversity and structure from the resequencing of 481 diverse soybean accessions, comprising 52 wild selections and 429 cultivated varieties (landraces and elites). This study identified evidence of distinct, mostly independent selection of lineages by particular geographic location.…”
Section: Rapidly Evolving Omics Approachesmentioning
confidence: 99%